Factors Predicting the Subjective Career Success of Nurses in University Hospitals - atichat, chanunthida; Abhicharttibutra, Kulwadee; Wichaikhum, Orn-anong (Nursing Journal CMU, 2022)
Subjective career success is an important factor related to performance efficiency and retention of nurses in their jobs. The objectives of this study were to study subjective career success and the factors predicting subjective career success of nurses in government university hospitals. The sample consisted of 180 nurses working in government university hospitals and was determined using multi-stage sampling. The instruments used consisted of the Subjective Career Success Scale and the Conditions of Work Effectiveness Question- naire. The reliability of the Subjective Career Success Scale was 0.86. For the sub-dimensions of the Conditions of Work Effectiveness Questionnaire, reliability values were 0.77, 0.69, 0.94, 1.00, 0.98 and 0.88. Data was analyzed using descriptive statistics and stepwise multiple regression analysis. The results showed that nurses at government university hospitals had overall subjective career success at a high level. The predicting factors for subjective career success were access to opportunities, formal power, access to support, access to information, and employment status, which could together explain 42.40% of subjective career success. The results can assist nursing administrators and hospital administrators in promoting structural empowerment to encourage nurses in government university hospitals to achieve more subjective career success. Finally, nurses will have more efficient performance and be retained in their employment.